The impact of isometric handgrip testing in left atrial reservoir function. (4th February 2022) - Uemoto, RV; Cancellier, R; Hortegal, R; De Freitas, RV; Maduro, Y; Paganelli, M; Grizante, M; Viana, R; Moriya, HT; Franchini, K
Abstract: Funding Acknowledgements: Type of funding sources: Public hospital(s). Main funding source(s): Fundação Adib Jatene Background Speckle tracking echocardiography (STE) allows accurate quantification of left atrial (LA) strain, thus allowing assessment of all phases of LA function (reservoir, conduit and contraction). Alterations in LA strain occur before changes in LA volumes, enabling early detection of LA dysfunction. In particular,  the peak of LA strain during the reservoir phase (LASr) seems to be of prognostic value in heart failure. LASr is essential to pool enough blood volume to fill the LV during the subsequent diastole. The main determinants of LA reservoir function include blood volume arriving from the right ventricle, LA relaxation, and LA compliance. Still, changes in atrioventricular plane movement during the ventricular systole have been considered an additional factor influencing LASr. The relative contribution of left ventricular afterload to LASr, however, has yet to be clearly defined. Purpose We aimed to study the LA function during changes in LV afterload induced by the handgrip maneuver in subjects without heart disease, applying LASr and strain curve shape analysis. Material and Methods We studied 31 subjects (47 ± 15 years) without evidence of heart disease. A comprehensive 2D echocardiography was performed. We recorded 3 beat clips with standard STE views of LV and LA in baseline conditions and then during pressure overload-induced by left handgrip (42 ± 8 kg) combined with simultaneous pneumatic constriction of the right arm and both lower limbs. The LV GLS and LASr were calculated offline by a blinded examinator using commercially available software. Furthermore, we extracted the raw data of the strain curves and post-processed these signals using custom software. The global curves were split into different cardiac cycle phases using the valve opening and closure times(Figure 1). Quadratic functions estimated strain curves during the ejection phase due to the acceleration involved in the phenomenon. Quadratic function linear coefficients, a component of strain rate, were used to assess the shape of deformation curves. Results: The handgrip maneuver caused mild reductions in LV strain: GLS baseline –19.07 % (±0.27) vs GLS handgrip -18.58% (±0.26) p = 0.02 (Figure 2A and C). Conversely, the LASr did not present significant changes: LASr baseline 33.82% (±0.84) vs LASr handgrip 32.96% (±0.85)  p= 0.18 (Figure 2B and C). For the analysis of the shape of strain curves, we obtained data from 29 subjects. We found significant differences in LV ejection linear coefficient (ELC): LV ELC baseline –158.30 (±8.52) vs LV ELC handgrip –144.62 (±8.02) p = 0.02. For LA reservoir linear coefficient (RLC), we also found significant differences: LA RLC baseline 240.30 (±17.19) vs LA RLC handgrip 212.61 (±15.62) p = 0.03 (Figure 2D). Conclusion(s) The left atrial reservoir function is affected by changes in LV afterload induced by the handgrip maneuver. Our data suggest that LV pressure overload mainly impact the shape of LA strain curve rather than LASr.